Nanoparticles as drug delivery systems in the treatment of oral squamous cell carcinoma: current status and recent progression - Cui, Shuxia; Liu, Hanzhe; Cui, Guanglin (Frontiers in Pharmacology, 2023)
Oral squamous cell carcinoma (OSCC) is a common human malignancy with an estimated incidence of around 377,713 new cases worldwide in 2020. Despite the advance in clinical management, some of OSCC patients still miss the opportunity of completable resection of tumor, and have to accept medical therapies, e.g., chemotherapy, radiotherapy, or immunotherapy when the disease develops into the advanced stage. However, these therapies have been reported to be far from ideal due to the low efficiency of conventional delivery approaches. To obtain a better therapeutic effect, considerable attempts have been made toward to develop an effective drug delivery system (DDS). Nanoparticles (NPs) including inorganic NPs, polymer NPs, lipid NP, extracellular vesicles and cell membrane-based NPs have been evaluated as the better DDS candidates that can specifically accumulate in the tumor microenvironment along with a large amount of blood vessels. Emerging evidence suggested that NPs formulated with anticancer drugs including chemotherapeutic drugs, radiotherapy and immunotarget antibodies could remarkably improve the release and increase concentration of these drugs at the tumor site and show a better therapeutic efficacy, suggesting that NPs might serve as promising DDSs in the treatment of OSCC. Therefore, we have conducted this review to summarize recent progression and current status of diverse NPs as DDSs in this research field.